DETERMINATION OF SEX FROM MASTOID TRIANGLE AMONG NORTH INDIANS (Journal of Forensic Medicine & Toxicology, 2019)
Introduction: Determination of sex from the skeleton is vital to medico-legal investigations. The mastoid region is analysed for determination of sex from fragmentary crania in forensic anthropology as it is one of the most protected region and resistant to damage due to its anatomical position at the base of the brain. Objective: The purpose of this study was to determine the existence of sexual dimorphism in the area of mastoid triangle related to three cranoimeteric points i.e. Porion, Asterion and Mastoidale among North Indians. Material and Methods: Material for the study consisted of 90 adult (above 18 years) human skulls (45 of either sex) of North Indians obtained from Anatomy and Forensic Medicine department of Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar. On each skull
Keywords: Asterion; Mastoidale; Porion; Sexual dimorphism; Mastoid triangle; North Indians